Fabrication of human oral mucosal epithelial cell sheets for treatment of esophageal ulceration by endoscopic submucosal dissection - Takagi, Ryo; Murakami, Daisuke; Kondo, Makoto; Ohki, Takeshi; Sasaki, Ryo; Mizutani, Manabu; Yamato, Masayuki; Nishida, Kohji; Namiki, Hideo; Yamamoto, Masakazu; Okano, Teruo (Gastrointestinal endoscopy, 2010)
Esophageal stenosis is one of the major complications of aggressive endoscopic resection. Tissue-engineered epithelial cell grafts have demonstrated effectiveness in promoting re-epithelialization and suppressing inflammation causing esophageal scarring and stenosis after endoscopic submucosal dissection (ESD) in an animal model. To confirm the reproducibility and efficacy of a human oral mucosal epithelial cell (hOMEC) sheet cultured on temperature-responsive surface in conformity with Good Manufacturing Practice guidelines. A preclinical study. Good Manufacturing Practice grade cell-processing center, animal laboratory. Canine esophageal ulcer models, which were made by ESD. Oral mucosal specimens were obtained from 7 healthy volunteers. Fabricated and transplanted hOMEC sheets were subjected to histological analysis. The reproducibility of the fabrication of hOMEC sheets was confirmed. In this method, animal-derived materials such as 3T3 feeder layer and fetal bovine serum were successfully excluded from the culture condition. Furthermore, the environment of the culture room and safety cabinet in the cell-processing center was maintained for obtaining sterility assurances during the fabrication. Transplanted hOMEC sheets after ESD were observed to graft onto canine esophageal ulcer surfaces. Small number of subjects, animal model. Cultured hOMEC sheets were fabricated without animal-derived materials and demonstrated efficacy as a medical device that promotes re-epithelialization of an esophageal ulcer after ESD.